Sidemen Songket Weaving as a Representation of Cultural Politics in Early Twentieth-Century Bali - Ni Made Rida Divayani; Desak Made Oka Purnawati; I Putu Hendra Mas Martayana; Jan Markus Vomel (Mahesa Research Center (PT. Mahesa Global Publishing), 2026)
This research is important to uncover how cultural commodities are used as instruments of legitimacy in colonial identity-building projects. The purpose of this research is to analyse the existence of Sidemen Songket Weaving in the context of Balinese cultural politics during the Baliseering era in the early 20th century. Through the imagination of Western Orientalism, the Dutch Colonial Government attempted to construct Bali as a pure cultural entity by protecting it from the influence of missions and Islamic preaching. This research uses historical methods that include heuristic stages (observation, literature studies, and oral traditions), verification, interpretation, and historiography. The results show that Sidemen Songket Weaving functions as a tool of colonial political representation to strengthen social stratification, class, and caste. Songket Weaving is transformed into a symbol of strength, wealth, and power, where ownership automatically attaches privileges. These findings indicate that the Dutch cultural preservation policy is not neutral but rather has political motives to control society's social structure. In conclusion, Balinese cultural politics has shifted the intrinsic function of Sidemen Songket Weaving into an instrument of identity politics that perpetuates feudalism under colonial control. This finding confirms that cultural objects are often engineered to maintain hierarchies for the sake of power stability.